2011
DOI: 10.1007/s11242-011-9811-0
|View full text |Cite
|
Sign up to set email alerts
|

Natural convection in a rotating anisotropic porous layer with internal heat generation

Abstract: In this article, linear and nonlinear thermal instability in a rotating anisotropic porous layer with heat source has been investigated. The extended Darcy model, which includes the time derivative and Coriolis term has been employed in the momentum equation. The linear theory has been performed by using normal mode technique, while nonlinear analysis is based on minimal representation of the truncated Fourier series having only two terms. The criteria for both stationary and oscillatory convection is derived … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
32
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 60 publications
(36 citation statements)
references
References 15 publications
4
32
0
Order By: Relevance
“…The literature on internal heating is much less extensive than that on external heating. Some latest studies are due to Bhadauria et al [22], Bhadauria [23] and Bhadauria et al ([24], [25], [26]). …”
Section: Introductionmentioning
confidence: 99%
“…The literature on internal heating is much less extensive than that on external heating. Some latest studies are due to Bhadauria et al [22], Bhadauria [23] and Bhadauria et al ([24], [25], [26]). …”
Section: Introductionmentioning
confidence: 99%
“…Capone et al [43] carried -27 -DOI: 10.5963/AMSA0301004 out the linear and nonlinear stability analysis of double-diffusive penetrative convection in an anisotropic porous layer with a constant throughflow via internal heat source. Recently Bhadauria group [44][45][46][47] have studied the problem of thermal instability in porous media with internal heating, considering various physical models. Double diffusive convection occurs in many systems in industry and nature, and in the present context, is of particular interest in the study of extraction of metals from ores where a mushy layer is formed during solidification of a metalic alloy.…”
mentioning
confidence: 99%
“…The thermal instability induced by uniform internal heat generation arising in a horizontal fluid layer has attracted the attention of many researchers [30][31][32][33][34][35][36][37][38]. It is found that an internal heat source decreases the stability of the fluid layer.…”
Section: Introductionmentioning
confidence: 99%